Clinical genetics involved in monogenic forms of hypertension in Chinese patients with early-onset hypertension and hypokalemia. (25th November 2020) - Fan, P; Zhang, D; Yang, K.Q; Zhang, Y; Lu, Y.T; Luo, F; Tian, T; Liu, Y.X; Zhou, X.L
Abstract: Background: Monogenic forms of hypertension are regarded as a group of conditions characterized by early-onset and resistant hypertension, electrolyte imbalance. These alterations stem from single mutations that lead to maladaptive excretion of potassium, and consequent hypokalemia. Purpose: This study aimed to analyze genes involved in monogenic forms of hypertension and clinical features in Chinese patients with early-onset hypertension and hypokalemia. Methods: A total of 129 unrelated Chinese patients (89 male and 40 females; average onset age of hypertension 25±5 years) with early-onset hypertension and hypokalemia. Patients with hypertension secondary to common causes, including renal disease and renovascular disease, aortic diseases, and obstructive sleep apnea were excluded. Genomic DNA were extracted from peripheral blood leucocytes of each subject. Using next-generation sequencing, we targeted and sequenced 42 genes related to monogenic forms of hypertension. All rare variants were confirmed by Sanger sequencing. Results: We detected 63 rare variants in 23 genes in 52 patients (40.3%). The variants in genes associated with pseudohypoaldosteronism, familial aldosteronism, pheochromocytoma or paraganglioma, and pseudohyperaldosteronism accounted for 22.2%, 23.8%, 20.6% and 11.1% respectively. Patients with rare variants had a significantly lower serum potassium (2.94±0.21 vs. 3.30±0.24 mmol/L, P<0.001) and family history of hypertension (67.3% vs. 31.2%, P<0.001). During 24±7.9 months of follow-up, several complication occurred, including stroke in 22 patients, coronary heart disease in 10, and chronic renal failure in 10. Factors associated with stroke were carrying rare variants (HR=4.371, 95% CI: 1.709–11.181, P=0.002), systolic blood pressure (HR=1.015, 95% CI: 1.004–1.037, P=0.015). Conclusions: This study revealed a wide genetic spectrum in Chinese patients with early-onset hypertension and hypokalemia. Genetic testing helps to differentiate the diagnosis of monogenic forms of hypertension in patients with hypertension and hypokalemia, and evaluates prognosis. Those patients carrying rare variants presented with a high risk of severe complications, stroke and needed close follow-up. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): CAMS Innovation Fund for Medical Sciences; the National Key Research and Development Program of China